2004
DOI: 10.1007/s11864-004-0004-8
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in management of the neck in head and neck cancer

Abstract: As definitive external radiation and multimodality organ preservation strategies (eg, combined chemotherapy and radiation therapy ) improve, the role of surgery is being re-examined in the management of locally advanced head and neck cancer. Consensus regarding the use of neck dissections for complete responders and incomplete responders has yet to be achieved and the data are surprisingly controversial. A possible benefit from neck dissection after a complete response of the primary tumor after CCRT or defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Randomized data addressing these questions and a trial addressing the accuracy of new imaging modalities, such as postchemotherapy and postradiation positron emission tomography scanning, across multiple institutions would be appropriate. 18 As a multidisciplinary department, we are aggressive in our treatment policy for isolated residual or recurrent neck disease, even after definitive EBRT.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized data addressing these questions and a trial addressing the accuracy of new imaging modalities, such as postchemotherapy and postradiation positron emission tomography scanning, across multiple institutions would be appropriate. 18 As a multidisciplinary department, we are aggressive in our treatment policy for isolated residual or recurrent neck disease, even after definitive EBRT.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale is that, among patients who exhibit a clinical CR in the neck following CRT, the recurrence rate in the neck is low (< 10%), and similar to that (8%) in patients with pathologically negative neck following ND. 8,16 Other level 2/3 studies 9,17,18 have also found that ND in patients who show a CR to CRT does not confer any benefit in terms of improved survival or reduction in nodal recurrence compared with a watch-and-wait policy. Importantly, a large retrospective cohort study found that 43% of patients showed CR on CT, with a control rate of 92% at 5 years.…”
Section: 14mentioning
confidence: 99%
“…However, studies are small, mainly retrospective, single-centre studies. Many authorities on head and neck (H&N) cancer and literature reviews 7,8 have stressed the need for a multicentre randomised trial to obtain an answer to this important question.…”
Section: Introductionmentioning
confidence: 99%
“…Some clinicians have even argued that the salvage rate for clinically detectable residual neck disease does not justify neck dissection being performed. Randomized trials addressing these questions, and a trial addressing the accuracy of new imaging modalities such as post chemotherapy and post radiation positron emission tomography scanning, across multiple institutions would be appropriate [50,51]. …”
Section: Management Of Positive Neck Nodesmentioning
confidence: 99%